2022
DOI: 10.1057/s41599-022-01102-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of digital technology on changing consumer behaviours with special reference to the home furnishing sector in Singapore

Abstract: The impact of digital technology has altered consumers’ choices for decades, which has fostered large amounts of eCommerce, including in the home furnishing business. Furthermore, due to the Coronavirus disease (COVID-19) pandemic, consumer behaviours have changed, with consumer satisfaction influencing purchasing initiatives and decision-making online. There is insufficient research on online purchasing behaviours in the home furnishing sector in the context of Singapore. The advent of digitisation and the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Furthermore, there is an indistinct limit through digitization cutting across technology and management, leading to the facilitation of new business models being integrated into methods [18], [19], concepts as well as tools of the digital environment, all tailored towards an emerging digital transformation. A corroborative recent study conducted an investigation aimed at finding evidence of how important technological innovations were with regard to practicing strategies for international business before and during the course of the COVID-19 pandemic [18].…”
Section: ) Mobile Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is an indistinct limit through digitization cutting across technology and management, leading to the facilitation of new business models being integrated into methods [18], [19], concepts as well as tools of the digital environment, all tailored towards an emerging digital transformation. A corroborative recent study conducted an investigation aimed at finding evidence of how important technological innovations were with regard to practicing strategies for international business before and during the course of the COVID-19 pandemic [18].…”
Section: ) Mobile Technologymentioning
confidence: 99%
“…However, there is a concern as to the user experiences both online and offline. In a recent study, the authors evaluated digital features responsible for the altering of customer behaviours to reveal underlying demands that analyses change in need and desires concerning furniture purchasing [19]. Their results revealed that when consumers engage online, they get motivated, thus resulting in a change in their attitudes and behaviours respectfully.…”
Section: ) Mobile Technologymentioning
confidence: 99%
“…New elements are "search" and "share" [12]. Based on the previous AIDMA model, the extended AISAS model is more appropriate to guide analysis on the Internet, which indicates the features of the Internet have an influence on consumers' attitudes, and at the same time, consumers cause corresponding purchase choices to fit the trend of the big data analysis [26]. Traditional modules are relatively limited in the integration of limited data from a macro level.…”
Section: Comparisonmentioning
confidence: 99%
“…One interesting effect is that the evolution of technology has greatly supported neuroscience research, leading to very rapid advances in the understanding of the brain and its application in different contexts such as business. In the business context, technological advances are increasingly rapid, especially since the pandemic, where a process of digitalisation of the economy affected both workers and customers (Cuesta-Valiño et al, 2022a;Rangaswamy et al, 2022;Singh and Shaurya, 2021). We live in a society where flexibility is a necessity, and happiness becomes an important variable to understand the effect of technologies on people (citizens, workers, customers).…”
Section: Introductionmentioning
confidence: 99%